Transcriptomic Identification of Drought-Related Genes and SSR Markers in Sudan Grass Based on RNA-Seq - Zhu, Yongqun; Wang, Xia; Huang, Linkai; Lin, Chaowen; Zhang, Xinquan; Xu, Wenzhi; Peng, Jianhua; Li, Zhou; Yan, Haidong; Luo, Fuxiang; Wang, Xie; Yao, Li; et al. (Frontiers in Plant Science, 2017)
Sudan grass (Sorghum sudanense) is an annual warm-season gramineous forage grass that is widely used as pasture, hay, and silage. However, drought stress severely impacts its yield, and there is limited information about the mechanisms of drought tolerance in Sudan grass. In this study, we used next-generation sequencing to identify differentially expressed genes (DEGs) in the Sudan grass variety Wulate No.1, and we developed simple sequence repeat (SSR) markers associated with drought stress. From 852,543,826 raw reads, nearly 816,854,366 clean reads were identified and used for analysis. A total of 80,686 unigenes were obtained via de novo assembly of the clean reads including 45,065 unigenes (55.9%) that were identified as coding sequences (CDSs). According to Gene Ontology analysis, 31,444 unigenes were annotated, 11,778 unigenes were identified to 25 categories in the clusters of orthologous groups of proteins (KOG) classification, and 11,223 unigenes were assigned to 280 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Additionally, there were 2,329 DEGs under a short-term of 25% polyethylene glycol (PEG) treatment, while 5,101 DEGs were identified under the long-term of 25% PEG treatment. DEGs were enriched in pathways of carbon fixation in photosynthetic organisms and plant hormone signal transduction which played a leading role in short-term of drought stress. However, DEGs were mainly enriched in pathway of plant hormone signal transduction that played an important role under long-term of drought stress. To increase accuracy, we excluded all the DEGs of all controls, specifically, five DEGs that were associated with high PEG concentrations were found through RNA-Seq. All five genes were up-regulated under drought stress, but the functions of the genes remain unclear. In addition, we identified 17,548 SSRs obtained from 80,686 unigenes. The newly identified drought tolerance DEGs will contribute to transgenic breeding efforts, while SSRs developed from high-throughput transcriptome data will facilitate marker-assisted selection for all traits in Sudan grass.